Perception of Secondary School Principals on Strategies for Improving Academic Performance: A Trajectory of UMkhanyakude Education District - Mbokazi, Msawenkosi Sandile; Mkhasibe, Rachel Gugu (Technium Social Sciences Journal, 2021)
The study outlines the findings from a case study that explored how the uMkhanyakude education district improved its academic performance in such challenging circumstances of the district. The performance chart of the district tabling results from 2008 to 2020 raised curiosity and interest to investigating the strategies employed by the district turn things around. The study adopted a qualitative method of enquiry employing document analysis and telephone interviews with principals of top-performing schools in the district. The findings revealed that transformative leadership, parental involvement in the form of izimbizo, adoption of schools with high enrolments, use of lead teachers, regular school visits, prescription of learner activities, well-planned extra-classes and introduction of Study camps raised learner academic performance in the district. The study recommends quality teaching and learning across the grades, parental involvement should be encouraged at all levels, two-way communication, regular support by the subject advisors and the unions.